Modeling and simulation of process of drying convective using differential model diffusive - convective solved by method of numerical finite volumes - Madson Linhares MagalhÃes (2016)
The consumption of energy is a main factor that determines the viability of any industrial process. Thermal dehydration is responsible for a high consumption of energy. In developed countries, 9 to 25% of the energy consumption of the national industry is attached to thermal dehydration. Thus, studying the dehydration process shows itself very promisor. In biological products, dehydration has a specific importance, the product conservation. The organic matter of the product and its water create a propitious medium for microorganisms proliferation that will deteriorate the product, making the product inappropriate for consumption. In this work, the modeling and simulation of a convective dehydration process using a diffusive-convective differential model solved by the finite volumes numeric method for predicting the behavior of the mean moisture content during the dehydration, defining molecular mass transfer and convective coefficients, and drawing moisture profiles of the interior of the solid. To evaluate the influence of internal and external resistances, the mass transfer Biot number was obtained. The implementation of the models of this work were made in PythonÂ using its scientific models for solving differential equations. This tool has been utilized because it is open source, has simple implementation when compared to other programming languages and has performance when performing simulations. As study of cases, experimental data of assisted convective dehydration by ultrasound of apple (Malus domestica L. var Royal Gala) cubes with 8 mm under the following operation conditions: 1, 2, 3 and 5 m/s for dehydration velocities, air flow temperature of 45ÂC and 60ÂC, presence and absence of ultrasound during the dehydration process and presence and absence of the pre-treatment with ultrasounds. The apple cubes of the experiments have 25 Â1g of mass. The dehydration has been performed until the removal of 80% of the initial mass of the cubes. The parameters, diffusivity and mass transfer coefficient, have been adjusted by Levenberg-Marquardt non-linear regression method. The results obtained in the simulations showed that the implemented model is very promisor, because it represents accurately the process. The values for diffusivity and mass transfer coefficient herein obtained were plausible. The influence of the air flow velocity, temperature and ultrasounds assistance and ultrasounds pre-treatments have been analyzed.